Efektivitas Model Pembelajaran Problem Solving terhadap Hasil Belajar Matematika Siswa Kelas V SD Negeri 80 Palembang - Emilda Savira Erjariza; Yasir Arafat; Susanti Faipri Selegi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Learning outcomes are a unit of value that is a benchmark in determining the success of learning. This low learning outcome can be caused by two factors, namely internal factors and external factors. Therefore, this research discusses the effectiveness of problem solving models on student learning outcomes. This research aims to determine the effectiveness of the problem solving learning model on the mathematics learning outcomes of class V students at SD Negeri 80 Palembang. This type of research is a quasi experimental design with a nonequivalent control group design type. The subject of this research is class V of SD Negeri 80 Palembang. This research data collection technique uses observation, tests and documentation. The data analysis technique using hypothesis testing assisted by SPSS version 26 resulted in a tcount value of 2.115 > ttable 2.045 so it can be concluded that there is a significant difference in the learning outcomes of students using the problem solving model at SD Negeri 80 Palembang